KAJIAN RESPONS PEUBAH TERHADAP BERBAGAI GUNCANGAN DALAM SISTEM PEMBENTUK PDB TANAMAN BAHAN MAKANAN MELALUI MODEL VECTOR AUTOREGRESSION - Anna Astrid Susanti; . . Aunuddin (FORUM STATISTIKA DAN KOMPUTASI, 2006)
It has been known that Gross Domestic Product (GDP) is one of the tools which can be used to measure the agriculture sector's performance. Since the agriculture's GDP is influenced by food crops' GDP, the measurement of agriculture's GDP is based on production value of the prior commodities of food crops such as rice and corn. Production is influenced by harvested area, yield, producer's price of commodities, and price of input factors such as fertilizers and pesticides. Vector Autoregression (VAR) model is one of the multivariate model that used to examine the relationship among variables which affect food crop's GDP. VAR can also be used for giving information about behavior of the variables in response to the various shocks. The objective of the study is to examine the response of a variable to the various shocks of the other variables by using response impulse function of VAR model. The study shows that harvested area significantly affects food crops' GDP on all term, but commodity prices and input factors prices just affect on short term. The results also show that inflations in agriculture sector will increase farmer's income and production effectively but the inflations are affected by input factor prices. Key words:: Food Crops' GDP, Vector Autoregression, Response Impulse Function